Enhanced Eyeblink Conditioning in Behaviorally Inhibited Individuals is Disrupted by Proactive Interference Following US Alone Pre-exposures - Allen, Michael Todd; Miller, Daniel P. (Frontiers in Behavioral Neuroscience, 2016)
Anxiety vulnerable individuals exhibit enhanced acquisition of conditioned eyeblinks as well as enhanced proactive interference from CS or US alone pre-exposures (Holloway et al., 2012). US alone pre-exposures disrupt subsequent CR acquisition to CS-US paired trials as compared to context pre-exposure controls. While Holloway et al., (2012) reported enhanced acquisition in high trait anxiety individuals in the context condition, anxiety vulnerability effects were not reported for the US alone pre-exposure group. It appears from the published data that there were no differences between high and low anxiety individuals in the US alone condition. In the work reported here, we sought to extend the findings of enhanced proactive interference with US alone pre-exposures to determine if the enhanced conditioning was disrupted by proactive interference procedures. We also were interested in the spontaneous eyeblinks during the pre-exposure phase of training. We categorized individuals as anxiety vulnerability or non-vulnerable individuals based scores on the Adult Measure of Behavioural Inhibition (AMBI). Sixty six participants received 60 trials consisting of 30 US alone or context alone pre-exposures followed by 30 CS-US trials. US alone pre-exposures not only disrupted CR acquisition overall, but behaviorally inhibited (BI) individuals exhibited enhanced proactive interference as compared to non-inhibited (NI) individuals. In addition, US alone pre-exposures disrupted the enhanced acquisition observed in BI individuals as compared to NI individuals following context alone pre-exposures. Differences were also found in rates of spontaneous eyeblinks between BI and NI individuals during context pre-exposure. Our findings will be discussed in the light of the neural substrates of eyeblink conditioning as well as possible factors such as hypervigilance in the amygdala and hippocampal systems, and possible learned helplessness. Applications of these findings of enhanced proactive interference in BI individuals to pre-exposure therapies to reduce anxiety disorders such as PTSD will be discussed.